Legal Aspects of Patient Care with Homecare Services Based on Pratama Clinical Practices - Sylvana, Yana; Utomo, St. Laksanto (Budapest International Research and Critics University, 2021)
Health services are evolving at a breakneck pace in the globalization era, especially in the middle of the Covid-19 pandemic, which has created massive patient lines at health care institutions. Homecare services are a viable option in the middle of the COVID-19 epidemic, as some people are hesitant to visit a hospital for fear of contracting the virus. On the other hand, when someone is ill, they require competent medical treatment. Homecare services are continuous and comprehensive care provided to an individual or family in their home and are included in the medical services available at the Primary Clinic, as defined in the Minister of Health Regulation Number 9 of 2014 about Clinics. However, with the increasing availability of homecare services, the issue is that an increasing number of health workers are providing homecare services independently, without involving established health facilities. If a health worker provides homecare services independently and does not adhere to administrative rules, it is inevitable that the homecare service will breach medical service standards, ethics, discipline, or the law.